Somatic symptoms and sleep quality as indicators of depression and suicide risk among Korean military conscripts. (May 2020) - Shim, Eun-Jung; Hwang, Heesung; Lee, Kwang-Min; Lee, Joo-Young; Lee, Sang Don; Baik, Myung-Jae; Shin, Min-Sup; Moon, Hoseok; Hahm, Bong-Jin
Highlights: Severity of somatic symptoms increased with depression and suicide risk. Somatic symptoms and perceived health can be a marker that help to identify individuals at suicide risk even without identified depression. Monitoring somatic and sleep complaints as well as perceived health can be an efficient and non-stigmatizing way of depression and suicide risk assessment. Abstract: This study examined whether somatic symptoms and sleep quality can be indicators of depression and suicide risk in Korean military conscripts. In October and November of 2016, a total of 1, 937 conscripts completed a survey that included the patient health questionnaire (PHQ) 9, PHQ15, the Mini International Neuropsychiatric Interview Plus suicidality module, and the Pittsburgh sleep quality index. Four groups were formed by depression and suicide risk status. Results from analyses of covariance indicated that overall, the severity of somatic symptoms and aspects of sleep quality were higher in conscripts with both depression and suicide risk, and greater associations of depression with somatic symptoms and sleep quality. The results of logistic regression analyses indicated that moderate to high levels of somatic symptoms and poorly perceived health were associated with the risk of depression and suicide, respectively. Poor sleep quality was associated with a higher risk of depression, but it was not significantly related to suicide risk after accounting for depression, which showed a greater association with suicide risk. Monitoring somatic and sleep complaints along with perceived health are needed as potential markers of depression and suicide risk among military conscripts.